An alternative review of facts, coincidences and past and future studies of the Lusi eruption. (August 2018) - Tingay, Mark; Manga, Michael; Rudolph, Maxwell L.; Davies, Richard
Abstract: The cause of the Lusi mud eruption remains controversial. The review by Miller and Mazzini (2017) firmly dismisses a role of drilling operations at the adjacent Banjarpanji-1 well and argues that the eruption was triggered by the M6.3 Yogyakarta earthquake some 254 km away. We disagree with these conclusions. We review drilling data and the daily drilling reports, which clearly confirm that the wellbore was not intact and that there was a subsurface blowout. Downhole pressure data from Lusi directly witness the birth of Lusi at the surface on the 29th of May 2006, indicating a direct connection between the well and the eruption. Furthermore, the daily drilling reports specifically state that Lusi activity was visibly altered on three separate occasions by attempts to kill the eruption by pumping dense fluid down the BJP-1 well, providing further evidence of a connection between the wellbore and Lusi. By comparison with other examples of newly initiated mud eruptions elsewhere by other earthquakes, the Yogyakarta earthquake was far away given its magnitude. The seismic energy density of the Yogyakarta earthquake was only 0.0043 J/m 3, which is less than a quarter of the minimum 0.019 J/m 3 seismic energy density that has ever been inferred to trigger other mud eruptions. We show that the Lusi area had previously experienced other shallow earthquakes with similar frequencies and stronger ground shaking that did not trigger an eruption. Finally, the data from the BJP-1 well indicates that there was no prior hydrodynamic connection between deep overpressured hydrothermal fluids and the shallow Kalibeng clays, and that there was no evidence of any liquefaction or remobilization of the Kalibeng clays induced by the earthquake. We thus strongly favor initiation by drilling and not an earthquake. Highlights: Cause of the Lusi eruption remains controversial, with proposals that it was triggered by either an earthquake or drilling. Drilling reports and data confirm that the wellbore was not intact, there was a blowout, and a direct surface connection. We show that the Yogyakarta earthquake was too far away given its magnitude to have initiated a new eruption. We strongly favor initiation of the eruption by drilling and not an earthquake.